2018
DOI: 10.1371/journal.pbio.2004037
|View full text |Cite
|
Sign up to set email alerts
|

The neural system of metacognition accompanying decision-making in the prefrontal cortex

Abstract: Decision-making is usually accompanied by metacognition, through which a decision maker monitors uncertainty regarding a decision and may then consequently revise the decision. These metacognitive processes can occur prior to or in the absence of feedback. However, the neural mechanisms of metacognition remain controversial. One theory proposes an independent neural system for metacognition in the prefrontal cortex (PFC); the other, that metacognitive processes coincide and overlap with the systems used for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 51 publications
6
76
0
2
Order By: Relevance
“…We employed the “decision‐redecision” paradigm that detailed in a previous study (Qiu et al, ). Briefly, the subject was instructed to make an initial decision regarding the moving direction of a random‐dot‐motion (RDM) stimulus (decision phase), and then was required to immediately make a second decision on the same stimulus (redecision phase).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We employed the “decision‐redecision” paradigm that detailed in a previous study (Qiu et al, ). Briefly, the subject was instructed to make an initial decision regarding the moving direction of a random‐dot‐motion (RDM) stimulus (decision phase), and then was required to immediately make a second decision on the same stimulus (redecision phase).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, when the decision uncertainty is high, the metacognitive processes should be evoked to revise the preceding decision. Several recent studies using functional MRI (fMRI) in simple perceptual decision‐making tasks have shown that the frontoparietal control network (FPCN) and the salience network (SN) are associated with metacognition accompanying the decision‐making task in the population of HC (Fleming et al, ; Morales et al, ; Qiu et al, ; Wan, Cheng, & Tanaka, ). The fMRI activities in these regions increase as decision uncertainty increases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations